Analisis tingkat kesiapan keamanan informasi menggunakan indeks kami 4.2 pada Politeknik Negeri Ketapang - Darmanto, Darmanto; Muhammad, Ar-Razy; Rustiarni, Rustiarni (Informasi Interaktif : Jurnal Informatika dan Teknologi Informasi, 2024)
In the era of information technology advancement, educational institutions, including Ketapang State Polytechnic, are increasingly relying on innovation by implementing information systems to maintain the smooth running of academic services and learning processes, especially in the midst of the Covid-19 pandemic. However, the extent to which the information security of these innovations has been maintained is still a question. This research aims to analyse the gap by conducting an assessment using the Information Security Index (ISI) 4.2, referring to the ISO 27001 standard, at Politeknik Negeri Ketapang. Although information technology has been integrated into operations at Politeknik Negeri Ketapang, the lack of in-depth analysis of information security brings uncertainty regarding the level of compliance with information security management standards. This research provides an in-depth analysis of governance, risk management, technology management, infrastructure, information security technology, and data protection. The results of this study not only provide an overview of the maturity level of information security at Politeknik Negeri Ketapang, but also provide concrete recommendations to improve the identified weaknesses. Analysis results based on KAMI Index 4.2 Ketapang State Polytechnic achieved a score of 16 with a high category out of a total of 50 in the use of Electronic Systems, signifying significant integration in business processes. The overall evaluation of the KAMI Index reached 453 out of 645, at level II-II+, indicating fulfilment of the Basic Framework for information security. Although compliant with information security management, there is a need for improved security measures, better supervision, and increased awareness of responsibility on the part of managers. Urgent improvements are required.